2007
DOI: 10.1111/j.1467-8535.2007.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of gender and gaming competence on attitudes towards using instructional games

Abstract: Malta. This paper is based on a 'work-in-progress' investigating collaborative gaming through an interactions-oriented approach. Piet Kommers is associate professor at the University of Twente. His specialities are new media technologies for education and society, Knowledge representation, teacher education and virtual reality. Based on his earlier work on conceptual media design he is one of the founders of structural graph equations for predicting user access in hypertext. Currently he is involved in restruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 26 publications
9
69
2
1
Order By: Relevance
“…In addition, females sometimes report that game-based learning is less interesting and enjoyable than males do (e.g., Bonanno & Kommers, 2008), although we note that these differences may be explained by other factors, especially amount of prior experience with game play and whether games are perceived as easy to use (Bourgonjon, Valcke, Soetaert, & Schellens, 2010). Gender differences have also been also associated with the dependent variable of empathy.…”
Section: Learning Outcomes and Control Variablesmentioning
confidence: 88%
“…In addition, females sometimes report that game-based learning is less interesting and enjoyable than males do (e.g., Bonanno & Kommers, 2008), although we note that these differences may be explained by other factors, especially amount of prior experience with game play and whether games are perceived as easy to use (Bourgonjon, Valcke, Soetaert, & Schellens, 2010). Gender differences have also been also associated with the dependent variable of empathy.…”
Section: Learning Outcomes and Control Variablesmentioning
confidence: 88%
“…Aside from differences that have been proven for computer usage in general, such as that males are more confident and skilled in handling computers [4], there is also particular evidence that males are specifically more engaged leisure game players than females [5]. Despite the popularity of computer games is rising in general, the majority of the medium's audience is still male [6].…”
Section: Computer Games and Gender Differencesmentioning
confidence: 99%
“…It could be shown that males have in general better computer skills and literacy [4]. Research results on online skills have shown that although there are no great gender differences in online abilities, females self-assess their skills significantly lower than males -which in turn may affect their online and usage behavior [22].…”
Section: Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…남학생은 여학생과 비교해 게임을 더 많이, 더 자주 이용할 뿐 아니라 상이한 게임유형을 선호한다 [10]. 또한 여성과 남성은 게임이용 태도도 매 우 상이한 것으로 나타난다 [11]. …”
unclassified